Cu-MOF derived Cu–C nanocomposites towards high performance electrochemical supercapacitors. Issue 8 (28th January 2020) - Wang, Jun; Rao, Mumin; Ye, Changchun; Qiu, Yongcai; Su, Wenjun; Zheng, Sheng-run; Fan, Jun; Cai, Song-liang; Zhang, Wei-Guang
Abstract : A new Cu–C nanocomposite derived from Cu-based metal–organic framework exhibits greatly improved electrochemical performance. Abstract : For the development of asymmetric supercapacitors with higher energy density, the study of new electrode materials with high capacitance is a priority. Herein, the electrochemical behavior of nano copper in alkaline electrolyte is first discovered. It is found that there are two obvious reversible redox symmetric peaks in the range of −0.8–0.2 V in the alkaline electrolyte, corresponding to the conversion of copper into cuprous ions, and then converting cuprous ions into copper ions, indicating that the nanocomposite electrode has the characteristics of a pseudocapacitive reaction. It has a specific capacitance of up to 318 F g −1 at a current density of 1 A g −1, which remains at nearly 100% after 10 000 cycles at the same current density. When assembled with a Ni(OH)2 -based electrode into an asymmetric supercapacitor, the device shows excellent capacitive behavior and good reaction reversibility. At 0.4 A g −1, the supercapacitor delivers a reversible capacity of 8.33 F g −1 with an energy density of 13.5 mW h g −1 . This study first discovers the electrochemical behavior of nano copper, which can provide a new research idea for further expanding the negative electrodes of supercapacitors with higher energy density.